Perbandingan Kemampuan Berpikir Kreatif dengan Penerapan Model Pembelajaran POE (Predict Observe Explain) dan POEW (Predict Observe Explain Write) pada Siswa SMA Negeri 1 Ngemplak Boyolali Tahun Pelajaran 2012/2013 - Nurul Qomariyah; Meti Indrowati; Joko Ariyanto (Universitas Sebelas Maret, 2014)
The research is aimed to find out the difference of creative thinking skills between application of POE (Predict Observe Explain) and POEW (Predict Observe Explain Write) learning model on student at SMA Negeri 1 Ngemplak Boyolali in academis year 2012/2013. The research belonged to the quasi experiment with research design Posttest Only Non-Equivalent Control Group Design. This research applied POE (Predict Observe Explain) learning model in the experimental group 1 and POEW (Predict Observe Explain Write)learning model in the experimental group 2. Population of research was the students in X degree SMA Negeri 1 Ngemplak Boyolali. The sampling used the cluster sampling was used as samply techniquel. The data collection technique was usedwerw test method belonged test shaped essay (for taking the data of students` creative thinking skills) and non-test method belonged documents method (for taking second data) and observation method (for taking the enforceability of the syntax and measure students` achievement psichomotor and affective as supporting data). Hypothesis testing belonged t-test. The results of the research shows that the mean of student`s capability of creative thinking in experiment group 1 higher than experiment group 2, it was 77,35 for experiment group 1 and 70,57 for experiment group 2. The result of hypothesis is analyze by t-test and it gets significant value 0,010 (sig<0,05), so there is difference of creative thinking skills between application of POE learning model and POEW learning model. Conclution of the research is there creative thinking skills between class use POE (Predict Observe Explain)learning model different withclass use POEW (Predict Observe Explain Write) learning model on student at SMA Negeri 1 Ngemplak Boyolali in academis year 2012/2013. Key Words: POE (Predict Observe Explain) Learning Model, POEW (Predict Observe Explain Write) Learning Model, Creative Thinking Skills